Personal Identification of Deceased Persons: An Overview of the Current Methods Based on Physical Appearance. Issue 3 (3rd October 2017) - Caplova, Zuzana; Obertova, Zuzana; Gibelli, Daniele M.; De Angelis, Danilo; Mazzarelli, Debora; Sforza, Chiarella; Cattaneo, Cristina
Abstract: The use of the physical appearance of the deceased has become more important because the available antemortem information for comparisons may consist only of a physical description and photographs. Twenty‐one articles dealing with the identification based on the physiognomic features of the human body were selected for review and were divided into four sections: (i) visual recognition, (ii) specific facial/body areas, (iii) biometrics, and (iv) dental superimposition. While opinions about the reliability of the visual recognition differ, the search showed that it has been used in mass disasters, even without testing its objectivity and reliability. Specific facial areas being explored for the identification of dead; however, their practical use is questioned, similarly to soft biometrics. The emerging dental superimposition seems to be the only standardized and successfully applied method for identification so far. More research is needed into a potential use of the individualizing features, considering that postmortem changes and technical difficulties may affect the identification.